IMPLEMENTASI METODE FUZZY MAMDANI PADA ALAT PENGERING KAIN BATIK PEWARNA INDIGOSOL MENGGUNAKAN MODEL GESER OTOMATIS - Pusada, Era Enggal Artis; Siswojo, Bambang; Maulana, Eka (Jurnal Mahasiswa TEUB, 2023)
Batik is a historical legacy that serves as a cultural heritage and a tourism commodity for the indigenous people of Indonesia. One of the synthetic dyes that can be utilized is the dye known as indigosol. Indigosol belongs to the group of oxidation dyes, where the color emerges after undergoing oxidation processes using oxidizers such as strong acids (HCl, H2SO4), with additional nitrite as a catalyst. To achieve an even and stronger color, optimal sunlight is required so that molecules can be excited perfectly. To attain optimal sunlight, a technology in the form of an automatic drying device is necessary to aid in the drying process. This helps optimize the drying results and anticipate rain. The device is equipped with UV lamps, an Arduino Uno microcontroller, a Light Dependent Resistor (LDR) sensor, a Raindrop sensor, and an Ultrasonic sensor (HCSR). The system of this device also employs logic that combines inputs from sensors and the microcontroller with outputs such as a DC motor and UV lamp, utilizing Fuzzy Mamdani logic. Fuzzy Mamdani logic is chosen due to its simplicity and ease of understanding compared to other fuzzy logics. Fuzzy Mamdani provides 5 membership sets for the LDR sensor and 3 membership sets for the Raindrop sensor, resulting in 1 output indicating the direction of the DC motor rotation. The use of this device significantly impacts the color output of indigosol-dyed batik fabric, especially during cloudy and rainy conditions, thanks to the UV lamp serving as a substitute for sunlight. The contribution of this device is quantifiable through the use of a histogram of images, depicting changes in color density in detail. Therefore, this device not only serves as a practical solution but also delivers a positive impact on the final outcomes in the Indonesian batik industry. Keywords: Fuzzy Mamdani, Indigosol Batik, Automatic Dryer, Ultrasonic Sensor, Raindrop Sensor, LDR Sensor